Implikatur Percakapan dalam Tayangan “ Tiga Bacapres Bicara Gagasan” - Simanjuntak, Dairi Sapta Rindu; Wulan, Eka Putri Saptari; Gustianingsih, Gustianingsih (eScience Humanity Journal, 2024)
The context of conversation in a discourse, especially political discourse which is currently trending, is very interesting to discuss. The context of conversation in pragmatics studies can be observed from the concept of implicature. Therefore, this research aims to explore the form of implicature utterances and the meaning of implicatures contained in the dialogue between the 2024 presidential candidates on the "3 Presidential Candidates Talk Ideas" program hosted by Najwa Shihab. This research uses a qualitative approach with content analysis method. The data source is a conversation video obtained from the YouTube channel. The research data is in the form of speech spoken by the speakers and presenters. Data presentation is carried out using an interactive model, namely data collection, data reduction, data verification and drawing conclusions. The findings of this research are that there are 14 implicature utterance data in the conversation. Implicature utterances are used by each presidential candidate. Even though implicature speech is used in the dialogue, the conversation still runs smoothly because both speakers understand the context and meaning of the speech being conveyed. The most important thing that determines the success of utterers in understanding the meaning and context of each utterance is the existence of similar experiences or perceptions even though it is not stated explicitly.